Factores Familiares Que Inciden En La Ideación Suicida De Los Adolescentes Entre 14 Y 17 Años, De Los Grados 10 y 11 de una Institución Educativa en Riohacha. (2022)
Good family functioning benefits the mental health of adolescents and acts as a protective factor in difficult situations that they must face and overcome. Therefore, the role of the family is probably one of the most discussed aspects. The purpose of this study was to identify the family factors that affect suicidal ideation in adolescents aged 14 to 17 in grades 10 and 11 of the María Dorisa López de Mea Educational Institution of the Special Tourist and Cultural District of Riohacha Grades